Religious Moderation Education in the Serambi Jombang Learning House Through the Study of The Interpretation of Moderate Verses - Tri Wahyudi Ramdhan; Saifuddin Saifuddin; Musohihul Hasan; Diana Trisnawati (STAI Syaichona Moh. Cholil Bangkalan, 2023)
Basic tenet that religiously motivated violence results from a narrow and intolerable interpretation of religion that has to be addressed and, as much as possible, restrained from spreading. The Serambi Jombang Learning House's study of the interpretation of moderate verses is intended to give guidance and knowledge of religious consciousness that is moderate, inclusive, and tolerant. A study on the interpretation of mild verses by 60 participants is conducted as part of this activity using the Action Research methodology. Selected verses, especially those pertaining to the ideals and principles of religious moderation, are delivered to the community as part of the activity material relevant to the topic of religious moderation education. The outcome of this activity is that it will be carried out in three stages, each of which will focus on the first subject of the activity, which is the study of non-Muslims in the Qur'an. The second discusses how the Qur'an reflects human ideals. The third discusses moderation in religion from the viewpoint of the Qur'an. Because there is a strong attitude toward moderation in religion, it is anticipated that this research will have positive effects and advantages, including helping people understand the community's religion, which tends to be moderate